1988
DOI: 10.1111/j.1432-1033.1988.tb13953.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid activation of human platelets by low concentrations of low‐density lipoprotein via phosphatidylinositol cycle

Abstract: The interaction of low-density lipoprotein (LDL) with the human platelet was investigated with regard to saturable high-affinity binding, shape change, cytosolic free Ca2+ concentration, phosphatidylinositol (PtdIns) turnover, and thromboxane Bz biosynthesis. The experiments show that LDL, at a concentration approximately 100 times lower than in plasma, causes platelet activation concomitantly with stimulation of the PtdIns cycle and thromboxane B2 formation, similarly to other activators of platelets. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…A 5-fold increase in ACTH-stimulated (50 nM) cortisol production was recorded with human LDL after prolonged stimulation but comparison with human HDL was not made (Rainey et al 1992). In addition, HDL, but not LDL, has also been reported to increase basal and AII-stimulated mineralocorticoid production by bovine zona glomerulosa cells (Knorr et al 1988). Our results from direct comparisons between LDL and HDL on basal and ACTH-stimulated steroid production are broadly in agreement with these studies (Koper et al 1985, Knorr et al 1988.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A 5-fold increase in ACTH-stimulated (50 nM) cortisol production was recorded with human LDL after prolonged stimulation but comparison with human HDL was not made (Rainey et al 1992). In addition, HDL, but not LDL, has also been reported to increase basal and AII-stimulated mineralocorticoid production by bovine zona glomerulosa cells (Knorr et al 1988). Our results from direct comparisons between LDL and HDL on basal and ACTH-stimulated steroid production are broadly in agreement with these studies (Koper et al 1985, Knorr et al 1988.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, HDL, but not LDL, has also been reported to increase basal and AII-stimulated mineralocorticoid production by bovine zona glomerulosa cells (Knorr et al 1988). Our results from direct comparisons between LDL and HDL on basal and ACTH-stimulated steroid production are broadly in agreement with these studies (Koper et al 1985, Knorr et al 1988. We observed that both LDL and HDL increased basal secretion but with LDL being more potent, whilst opposite effects were observed on ACTHstimulated steroidogenesis with HDL having a greater effect.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet aggregation stimulated by a variety of means, including by thrombin and ADP, is reduced by HDL, and the lipoprotein also decreases thromboxane A2 and 12-hydroxy-eicosatetraenoic acid release from platelets ( 85,86 ). HDL activates p38MAPK in platelets ( 87 ), and it attenuates intracellular calcium mobilization invoked by LDL cholesterol ( 88 ). ApoA-Irich HDL may exert its actions on platelets via SR-BI, whereas responses to apoE-rich HDL are likely mediated by a splice variant of the LDL receptor family member apoER2 or Lrp8 ( 85,89 ).…”
Section: Plateletsmentioning
confidence: 99%
“…Among the signal transducing elements that are activated by LDL are protein kinase C (PKC) (21,22), Ca 2ϩ mobi-lization (20,23,24) and phosphoinositide turnover (20,21,24,25). The faster collagen-induced secretion in LDL-treated platelets critically depends on ligand-induced outside-in signaling via integrin ␣ IIb ␤ 3 .…”
mentioning
confidence: 99%